Use of Low Frequency Ultrasound for The Treatment of Diseases of The Nasal Cavity and Adjacent Sinuses (Texas Journal of Medical Science, 2023)
This article explores the use of low-frequency ultrasound in the treatment of diseases of the nasal cavity and paranasal sinuses. Low-frequency ultrasound is a modern method of physical therapy that can penetrate deeply into tissue and cause various biological reactions. Research shows that the use of lowfrequency ultrasound can have a positive effect on the condition of the nasal cavity and paranasal sinuses, improving mucociliary clearance, facilitating the outflow of secretions and improving the penetration of antiseptic solutions into tissues. The combined use of low-frequency ultrasound with antiseptics and other medications can also enhance their effect on the affected areas. It is important to continue research to determine the optimal parameters for use and safety of this method. Overall, the use of low-frequency ultrasound represents a promising approach to developing more effective treatments for diseases of the nasal cavity and paranasal sinuses